Identifying outcomes reported in exercise interventions in oesophagogastric cancer survivors: a systematic review - Louise O’Connor; Emily Smyth; Annemarie E. Bennett; Valerie Smith; Linda O’Neill; John V. Reynolds; Juliette Hussey; Emer Guinan (BMC Cancer, 2021)
Abstract Background Research investigating exercise interventions in oesophagogastric cancer survivors is sparse, and the outcomes are varied. The aim of this systematic review is to identify the domains and outcomes reported in exercise interventions in oesophagogastric cancer survivors to be included in a Delphi study, with a view to informing the development of a core outcome set (COS). Methods EMBASE, PubMed, CINHAL, Cochrane Library, SCOPUS, and PEDro were searched up to March 2020 using a predefined search strategy. The outcomes identified during data extraction were categorised using the core areas outlined in the OMERACT Filter 2.0. Results Fourteen domains and 63 outcomes were identified. The most frequently reported outcomes were in the domains of quality of life using the EORTC-QLQ-C30 questionnaire and the relevant disease-specific modules (100%), exercise capacity/fitness/physical function (100%), anthropometrics (83.33%), physical activity (66.67%), and biomarker analysis (50%). Conclusion This systematic review quantifies and describes the domains and outcomes examined in exercise interventions in oesophagogastric cancer survivors. Some inconsistency exists within the domains and outcomes used, and little attention was given to nutritional or economic endpoints. In order to develop a COS, a Delphi consensus process with key stakeholders is needed to identify the relevant domains and outcomes for inclusion.